Reliability Assessment Based on Structural Health Monitoring Data and Bayesian Updating of Structural Models - Uzun, Ertuğrul Türker; Aktaş, Engin; Hızal, Çağlayan (01. Izmir Institute of Technology, 2024)
Finite element (FE) models are commonly used in numerical modeling of structures, but their assumptions can lead to inaccuracies and uncertainties. To address this, FE model update methods have been developed, calibrating the model based on structural health monitoring (SHM) data. However, a general framework for realistic life cycle performance assessment of structures using monitored data has not yet been presented. Bayesian modeling can characterize uncertain structural parameters as random variables, but it is complex and time-consuming. Metamodeling techniques, which are effective stochastic predictors, can be used to decrease the computational burden of model updating. Adapting a Polynomial-Chaos-Kriging (PCK) metamodeling technique to Bayesian model updating in order to reduce uncertainty and circumvent computational challenges using SHM data in order to assess the reliability of structures more precisely is the objective of this research. Therefore, the effectiveness of the proposed method has been tried and demonstrated through experimental and numerical studies. An experimental study of a bridge column is used to evaluate the reliability of structures subjected to various corrosion effects. As a result, the proposed solution method reduces computational costs and enables an updated FE model to be closer to real structure measurements. The updated models are found to be more reliable in reliability evaluations, providing more accurate predictions on issues like structure safety, service life, and maintenance cost compared to non-updated models.

Sonlu elemanlar (FE) modelleri yapıların sayısal modellenmesinde yaygın olarak kullanılmaktadır ancak varsayımları yanlışlıklara ve belirsizliklere yol açabilmektedir. Bu sorunu çözmek için, modeli yapısal sağlık izleme (SHM) verilerine dayalı olarak kalibre eden FE modeli güncelleme yöntemleri geliştirilmiştir. Ancak izlenen verileri kullanan yapıların gerçekçi yaşam döngüsü performans değerlendirmesine yönelik genel bir çerçeve henüz sunulmamıştır. Bayes modellemesi belirsiz yapısal parametreleri rastgele değişkenler olarak karakterize edebilir, ancak karmaşık ve zaman alıcıdır. Etkili stokastik tahminciler olan meta-modelleme teknikleri, model güncellemenin hesaplama yükünü azaltmak için kullanılabilir. Yapıların güvenilirliğini daha kesin bir şekilde değerlendirmek için SHM verilerini kullanarak belirsizliği azaltmak ve hesaplama zorluklarını aşmak amacıyla Polynomial-Chaos-Kriging (PCK) meta-modelleme tekniğini Bayezyen model güncellemesine uyarlamak bu araştırmanın amacıdır. Bu nedenle önerilen yöntemin etkinliği deneysel ve sayısal çalışmalarla denenmiş ve gösterilmiştir. Çeşitli korozyon etkilerine maruz kalan yapıların güvenilirliğini değerlendirmek için bir köprü kolonunun deneysel bir çalışması kullanılır. Sonuç olarak, önerilen çözüm yöntemi hesaplama maliyetlerini azaltır ve güncellenmiş bir FE modelinin gerçek yapı ölçümlerine daha yakın olmasını sağlar. Güncellenen modellerin güvenilirlik değerlendirmelerinde daha güvenilir olduğu, yapı güvenliği, servis ömrü, bakım maliyeti gibi konularda güncellenmeyen modellere göre daha doğru tahminler sağladığı görüldü.
Yapısal sağlık izleme verilerine ve yapısal modellerin bayes güncellemesine dayalı güvenilirlik değerlendirmesi
Thesis (Doctoral)--İzmir Institute of Technology, Civil Engineering, Izmir, 2024
Includes bibliographical references (leaves. 110-121)
Text in English; Abstract: Turkish and English
Keywords: Structural health monitoring; Bayesian statistical decision theory; Finite element method